Intracranial aneurysms at higher clinical risk for rupture demonstrate increased wall enhancement and thinning on multicontrast 3D vessel wall MRI - Hartman, Jason Brett (Br J Radiol, 2019)
OBJECTIVE: Identification of aneurysms at risk for rupture is important and challenging. We sought to evaluate if intracranial vessel wall (IVW) imaging characteristics of unruptured aneurysms correlate with clinical risk factors for rupture. METHODS: Patients with unruptured intracranial aneurysms were prospectively recruited and underwent a multi contrast 3D IVW protocol between April 6, 2016 and August 29, 2017. Two independent raters, blinded to aneurysm vulnerability, evaluated each aneurysm for wall enhancement, extent of enhancement in terms of the numbers of quadrants enhancing circumferentially, intensity of enhancement, and qualitative wall thinning. PHASES score was calculated for each aneurysm. Univariate logistic regression analysis was used to compare IVW characteristics between aneurysms at higher clinical risk for rupture (PHASES score > 3) and lower clinical risk for rupture (PHASES score ≤ 3). RESULTS: 45 patients with 65 unruptured aneurysms were analyzed; 38 aneurysms with PHASES score > 3 (58%) and 27 aneurysms with PHASES score ≤ 3 (42%). Aneurysms with PHASES score > 3 were more likely to demonstrate enhancement (42.1% vs 14.8%, p = 0.022), greater extent of enhancement (mean: 2.9 vs 2.2 quadrants, p = 0.063), and wall thinning (9.2% vs 0%, p = 0.044). Inter-reader agreement was moderate-to-good for the presence (κ = 0.64), extent (κ = 0.64), and intensity of enhancement (κ = 0.60) but relatively low for wall thinning (κ = 0.25). CONCLUSION: Aneurysms at higher risk of rupture by PHASES score are more likely to demonstrate wall enhancement, more diffuse enhancement, and wall thinning on IVW. ADVANCES IN KNOWLEDGE: This study prospectively compares IVW-detected wall enhancement and thinning between unruptured aneurysms stratified into high and low risk groups by clinical scores (PHASES) of vulnerability.